A Phenomenological Inquiry of Identity Development, Same‐Sex Attraction, and Religious Upbringing. Issue 1 (11th April 2018) - Crockett, Jamie E.; Cashwell, Craig S.; Marszalek, John F.; Willis, Ben T.
Abstract : Growing up in religious/spiritual communities often creates identity issues for lesbian and gay individuals. In this phenomenological study, the authors investigated the experiences of 25 lesbian and gay individuals who self‐identified as having been raised within organized religious communities. Participants described that these communities were affirming, tolerant, or nonaffirming. Accordingly, emergent themes indicated that the current spiritual lives of participants varied greatly depending on their experiences of identity integration and affirmation. Implications for counselors and researchers are discussed.